Boron nutritional management in Australian forest plantations - John Turner; Jim Knott; Phil Green; Sue Turner (Trees, Forests and People, 2021)
Boron deficiency is a major cause of loss in productivity and value in East Coast Australian radiata pine plantations. Most forest soils have an adequate supply of boron to support tree growth, but boron deficiencies are not uncommon, and where they exist, tree growth is retarded and stem dieback is frequent. Symptoms of deficiency include dieback and resprouting, often leading to trees with bushy appearance or multiple leadering. In Eastern Australia boron deficiency has been noted on a range of site and environmental conditions, and it is the variability that has made nutritional aspects difficult to study in the field. This paper is a compilation of field studies and surveys related to boron nutrition in radiata pine. The distribution and cycling of boron show a constant increase with increasing age, and in a moderate quality stand there was about 2.1 kg B ha−1 accumulated in above-ground biomass by age 25 years, and, whereas with macronutrients there is a peak in uptake near crown closure, followed by a decline, the boron uptake plateaus from about age 5 years at about 200 g B ha−1 yr−1. There is no evidence of net re-translocation of boron from senescing tissues or in heartwood formation; further, boron increases in concentration as tissues age, with increasing demands throughout the rotation. Boron is primarily taken up from the soil and quantities generally relate to soil parent material however there are significant inputs of boron in rainfall from maritime sources, as shown from rainfall analyses. A large proportion of soil boron is related to organic matter and is released with mineralisation that has a significant effect when conditions are dry and mineralisation low.An extensive data set of over 9,000 samples on foliage boron was used to analyse relationships of stand and site factors to boron foliage levels and develop risk categories for identifying boron deficiency. Foliage analysis is a valuable pool for determining boron status, however it is best used when plantations are at least 3–5 years old, by which time dieback symptoms are often occurring on susceptible sites, hence a system to identify high risk sites at time of planting is required. Required or desirable concentrations of foliage boron have previously been set at, or above, 8–10 mg kg−1 based on presence or absence of symptoms, but analysis of critical levels based on growth indicates a desirable boron concentration is closer to 20 mg kg−1 and relationships with wood quality may mean the figure is greater (probably 30 mg kg−1).Factors analysed in relation to boron concentration included soil parent material (Parent Rock Code or PRC), rainfall, distance from coast, elevation, stand age, rotation, land use prior to plantation establishment and use of boron fertilizer, these all being consistently available for all sites. Differences were found for the non-fertilized sites between PRC and prior land use, and there were declines in boron with change in rotation. For all unfertilized data, and for PRC's individually, the most significant factor was stand age followed by distance from the coast. High risk categories were identified on site factors. Boron deficiency can be alleviated by boron fertilizer application, however results on uptake and length of time of efficacy are variable, depending upon fertilizer composition, fertilizer form and method of application and soil type. Sodium borate is rapidly taken up but has low soil retention, calcium borate and hydroboracite have slow-release rates but longer retention, while sodium-calcium borate has produced the most consistent results, especially in pellet form, as opposed to crushed and sieved rock. Applications are best on a single tree basis immediately after planting, at a rate of 5–7 g B per tree; broadcast applications to young stands have had limited success.